Percutaneous Method of Management of Simple Bone Cyst - O. P. Lakhwani (Case Reports in Orthopedics)
Introduction. Simple bone cyst or unicameral bone cysts are benign osteolytic lesions seen in metadiaphysis of long bones in growing children. Various treatment modalities with variable outcomes have been described in the literature. The case report illustrates the surgical technique of minimally invasive method of treatment. Case Study. A 14-year-old boy was diagnosed as active simple bone cyst proximal humerus with pathological fracture. The patient was treated by minimally invasive percutaneous curettage with titanium elastic nail (TENS) and allogenic bone grafting mixed with bone marrow under image intensifier guidance. Results. Pathological fracture was healed and allograft filled in the cavity was well taken up. The patient achieved full range of motion with successful outcome. Conclusion. Minimally invasive percutaneous method using elastic intramedullary nail gives benefit of curettage cyst decompression and stabilization of fracture. Allogenic bone graft fills the cavity and healing of lesion by osteointegration. This method may be considered with advantage of minimally invasive technique in treatment of benign cystic lesions of bone, and the level of evidence was therapeutic level V.